Decreased hippocampal neurite density in late-middle-aged adults following prenatal exposure to higher levels of maternal inflammation - Raana A. Mohyee; Blake L. Elliott; Madeline R. Pike; Emma Smith; Ann M. Kring; Ingrid R. Olson; Elizabeth C. Breen; Barbara A. Cohn; Piera M. Cirillo; Nickilou Y. Krigbaum; Thomas M. Olino; Mark D’Esposito; et al. (Proceedings of the National Academy of Sciences, 2025)
In animal models, exposure to heightened maternal inflammation in utero is associated with altered offspring hippocampal development, including reduced dendritic arborization and density. However, the effects of prenatal maternal inflammation (PNMI) on offspring hippocampal microstructure in humans remain unclear. Here, we examined the relationship between exposure to PNMI and neurite density in the hippocampus and its subfields among offspring during late middle age. Participants included 72 mother–offspring dyads from the Child Health and Development Studies (CHDS) cohort. Data for four inflammatory biomarkers (IL-6, IL-8, IL-1 receptor antagonist [IL-1RA], and soluble Tumor Necrosis Factor (TNF) receptor-II) were available from first- and second-trimester maternal sera. Neurite density in the offspring hippocampus and its subfields was estimated using microstructural modeling of offspring’s diffusion-weighted MRI data (mean age of offspring at imaging = 59 y; 51% male). We estimated the relationship between each biomarker and region-of-interest’s neurite density. Higher first-trimester maternal IL-1RA and IL-6 levels were associated with lower offspring hippocampal neurite density. These relationships were specific to the Cornu Ammonis 3, Cornu Ammonis 4, dentate gyrus, and subiculum subfields. In addition, higher second-trimester IL-6 was associated with lower subiculum neurite density. Our findings reveal that exposure to heightened prenatal levels of maternal inflammation is linked to altered offspring hippocampal microstructure in late middle age, which could have implications for memory decreases during this period and may be relevant for understanding the risk of aging-related cognitive changes.